Retinal degeneration in rpgra mutant zebrafish - Liu, Xiliang; Han, Shanshan; Liu, Fei; Yu, Shanshan; Qin, Yayun; Li, Jingzhen; Jia, Danna; Gao, Pan; Chen, Xiang; Tang, Zhaohui; Liu, Mugen; Huang, Yuwen (Frontiers in Cell and Developmental Biology, 2023)
Pathogenic mutations in RPGRORF15, one of two major human RPGR isoforms, were responsible for most X-linked retinitis pigmentosa cases. Previous studies have shown that RPGR plays a critical role in ciliary protein transport. However, the precise mechanisms of disease triggered by RPGRORF15 mutations have yet to be clearly defined. There are two homologous genes in zebrafish, rpgra and rpgrb. Zebrafish rpgra has a single transcript homologous to human RPGRORF15, rpgrb has two major transcripts: rpgrb ex1-17 and rpgrb ORF15, similar to human RPGR ex1-19 and RPGR ORF15, respectively. rpgrb knockdown in zebrafish resulted in both abnormal development and increased cell death in the dysplastic retina. However, the impact of knocking down rpgra in zebrafish remains undetermined. Here, we utilized transcription activator-like effector nuclease (TALEN) to generate a rpgra mutant zebrafish harboring the c.1675_1678delins21 mutation, aiming to investigate the role of rpgra in zebrafish retina. Despite normal morphological development of the retina at 5 days post-fertilization, visual dysfunction was observed in the mutant zebrafish. Further histological and immunofluorescence assays indicated that rpgra mutant zebrafish retina photoreceptors progressively degenerated begin at 3-6month. Additionally, mislocalization of cone outer segment proteins (Opn1lw and Gnb3) and accumulation of vacuole-like structures around the connecting cilium below the OSs were observed in mutant zebrafish. Furthermore, Rab8a, a key regulator of opsin-carrier vesicle trafficking, exhibited decreased expression and evident mislocalization in mutant zebrafish. Collectively, our data suggested Rpgra is necessary for ciliary transport of cone-associated proteins, and further investigation is required to determine its function in rods. The rpgra mutant zebrafish constructed in this study may help us gain better understanding of the molecular mechanism of retinal degeneration caused by RPGRORF15 mutation and find some useful treatment in the future.